Body mass index as predictor of carpal tunnel syndrome among garment workers - Merijanti, Lie T. (Universa Medicina, 2009)
Of the nerve entrapment syndromes the most well-known is the carpal tunnel syndrome (CTS) involving the median nerve. In the field of occupational medicine this condition is categorized as an occupational disease, for which industrial workers may claim compensation if the CTS occurs as a consequence of their job. However, although several occupational risk factors have been suggested as causing the development of CTS, a definitive role of work activities as the central cause of CTS is unclear. The aim of the present study was to evaluate both non-occupational and occupational factors associated with CTS in garment home-industry workers. A cross-sectional study was performed from April to June 2008 in the garment home industry in North Jakarta. A total of 99 workers, consisting of 45 males and 54 females were included in this study. Historical data were obtained from a self-administered detailed questionnaire, while anthropometric and provocative median nerve test variables were measured directly. The results showed that body mass index (BMI) was a significant predictor of CTS in male workers (p=0.031), while the risk of CTS was three-fold higher in female workers using hormonal contraceptives (Prevalence Ratio/PR = 3.3 ; 95% Confidence of Interval/CI = 1.0 – 10.5). In conclusion it appears that BMI and hormonal contraceptive use were CTS predictors.